The Effect of Sustainable Finance, Intellectual Capital, and Investment Opportunity Set on Financial Performance - Saskia Indriani; Erna Setiany (Transpublika Publisher, 2024)
The objective of this research is to examine the impact of sustainable finance, intellectual capital, and investment opportunity on the financial performance of 34 banking firms listed on the Indonesia Stock Exchange. Data from the years 2018 to 2022 were utilized for this study. Purposive sampling was employed as the sampling method. The required data was gathered from annual reports accessible on the websites of the respective companies. Panel data regression was utilized for data analysis. The initial hypothesis testing revealed that sustainable finance did not notably impact the financial performance of banking firms listed on the Indonesia Stock Exchange. Contrarily, the subsequent tests showed that environmental performance and investment opportunity set had a beneficial and significant influence on the financial performance of these banking companies.